Tajdid, Islah, and Civilizational Renewal in Islam: by Mohammed Hashim Kamali (American Journal of Islam and Society, 2020)
Mohammed Hashim Kamali, an Islamic scholar and specialist in Islamic law and jurisprudence, possesses higher degrees in Comparative Law from University of London, and taught at McGill University (Canada) and International Islamic University, Malaysia for most of his academic career. Since 2008, he is the Founding Chairman and CEO of International Institute of Advanced Islamic Studies (IAIS), Malaysia and editor-in-chief of its journal Islam and Civilizational Renewal (ICR) (for details, see www.iais.org.my and www.hashimkamali.com).Download